EVALUASI SYARIAH DAN PENGEMBANGAN MODEL CRYPTOCURRENCY STABLECOIN: PENDEKATAN BERBASIS FIAT VS. BERBASIS EMAS - Widjiantoro, Surya Tegar; Segati, Ahda; Marpaung, Muslim (JSE: Jurnal Sharia Economica, 2026)
This study discusses the comparison between fiat-based stablecoins and gold-based stablecoins from the perspective of Islamic economics, particularly in the context of the high price volatility of cryptocurrencies. The background of this research is the need for stable digital financial instruments that comply with sharia principles, considering that stablecoins have emerged as a solution to cryptocurrency value fluctuations but raise questions regarding their compatibility with Islamic law. The research method used is a literature review by analyzing various stablecoin models and examining literature related to sharia principles in finance, such as the prohibition of riba (usury), gharar (uncertainty), maysir (gambling), and the importance of underlying assets. The results show that gold-based stablecoins are more aligned with the concept of money in Islamic economics because they are backed by clear physical assets, whereas fiat-based stablecoins contain elements of riba due to seigniorage and the lack of clarity in intrinsic value. The conclusion of this study asserts that, from an Islamic economic perspective, gold-based stablecoins are more appropriate to be developed as sharia-compliant digital transaction instruments, while fiat-based stablecoins still have several aspects that need further review regarding sharia compliance.